Peran Keluarga Dalam Membentuk Kecerdasan Spiritual Anak Usia Prasekolah Dusun Sawangan RT 03/RW 01, Karanganyar, Purwanegara, Banjarnegara - Elvina Tri Astuti; Ahmad Zuhdi; Siti Lailiyah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
The family in RI Law No. 52 of 2009 is defined as the smallest unit in society, which includes husband and wife, or husband, or wife and children, or father and mother and their children. Family harmony can affect the formation of children's intelligence because family is the most important foundation in a child's life. Intelligence itself is interpreted as thinking. Spiritual intelligence is a complete soul or thought that is formed from an activity to solve problems in accordance with the meaning contained therein. Nowadays, there are many families where the intelligence of their children is not balanced because of their busy schedules, low awareness of the importance of balancing the formation of their children's intelligence, and parents' lack of knowledge about spiritual intelligence. This research was conducted using a qualitative field method. With data collection techniques, namely observation, interviews and documentation. With data analysis techniques, namely data reduction, data presentation and drawing conclusions. The results obtained from this study were only about 35.3% of parents who understood well about spiritual intelligence, 64.7% of parents who thought that spiritual intelligence was only closely related to learning/knowledge about religion and had nothing to do with other. This study also found that 27.7% of pre-school-age children in Sawangan hamlet, RT 03/RW 01, had good spiritual intelligence and had been formed according to indicators in spiritual intelligence, although it could be said that it was not optimal. Meanwhile, as many as 72.2% of pre-school aged children ranging from 2 to 4 years of age have spiritual intelligence that has not been formed properly so that it does not meet the indicators of spiritual intelligence itself.